Literature Review of Accreditation Systems in Higher Education - Nelson Duarte; Ricardo Vardasca (MDPI AG, 2023)
This study investigates the accreditation processes in higher education across various countries, focusing on the time and bureaucratic burden associated with accrediting new courses. The aim is to identify strategies to accelerate the accreditation process for new courses in higher education institutions. A comprehensive literature review was conducted to achieve this objective, examining the accreditation processes in Portugal, Spain, the United States, France, China, Japan, Sweden, the United Kingdom, India, and Germany. The study's key findings revealed that the accreditation process is generally efficient in most countries, with courses receiving accreditation within a reasonable timeframe. However, the process can be more complex and time-consuming for institutions seeking accreditation for the first time or offering new or innovative courses. Institutions must meet all established criteria and promptly provide all required documentation to expedite the accreditation process. The implications of these findings suggest that higher education institutions should collaborate closely with relevant accrediting agencies to ensure a streamlined accreditation process. Institutions should also consider agency requirements and course specialization when developing new courses. Furthermore, governments play a crucial role in promoting transparency and competition among higher education institutions, which can lead to enhanced quality assurance and increased customer satisfaction in the education sector.